THE RIGHT OF TRADE UNIONS TO DISCLOSURE OF INFORMATION UNDER THE LRA: BALANCING THE INTERESTS OF TRADE UNIONS AND EMPLOYERS - ME Manamela (Obiter, 2018)
Access to information promotes values of transparency, openness, and accountability that are important for a progressive constitutional democracy. Section 32(1) of the Constitution of the Republic of South Africa, 1996 (hereinafter “the Constitution”) provides that “everyone has the right of access to information held by the state or by another person that is required for the exercise or protection of any rights”. It is submitted that the word “everyone” in this provision, includes trade unions and employees and that the words “another person” in the provision include employers. Employees and their trade unions, therefore, have the right of access to information that the employer has, which may be required for the exercise or protection of their rights. Section 32(2) of the Constitution, further provides that “legislation may be enacted to give effect to this right”. The Promotion of Access to Information Act (2 of 2000 (PAIA)) gives effect to the right of access to information in general, however, for purposes of this discussion, the Labour Relations Act (66 of 1995 (LRA)) gives effect to the right through a number of provisions; including its sections 16 and 189. While section 16 requires the employer to disclose to a representative trade union all relevant information that will enable trade union representatives to effectively perform functions, which are listed in section 14(4); section 189 regulates the disclosure of information in the context of dismissals based on operational reasons of the employer. The above is in line with the International Labour Organisation’s (ILO) Collective Bargaining Standards Recommendation 163 (1981) which provides that “measures adapted to national conditions should be taken, if necessary so that parties have access to the information required by meaningful negotiation”. Section 23(5) of the Constitution grants every trade union a right to engage in collective bargaining. This right is protected and supported through provisions mentioned above which permit trade unions to request relevant information, which is important for the effective exercise of the right. This, however, has often proved to be problematic; largely due to the fact that on the one hand, trade unions need information, while on the other hand, employers sometimes regard this as an invasion of privacy. Employers often refuse to divulge information requested by trade unions as they think that the disclosure of information will also negatively affect their bargaining power or that sensitive information may get to competitors and jeopardize their business. Business South Africa (BUSA) raised concerns regarding the right to disclosure of information in its submissions to the National Economic Development and Labour Council (NEDLAC) during the drafting of the LRA as it regarded the obligation to disclose information to trade unions as a threat and an encroachment into management prerogatives. This argument was largely based on commercial secrecy; confidentiality and that disclosure of information would impede effective decision-making. In view thereof, it is important that there be a balance between the right of trade unions to information and the employer’s duty to disclose the information. This analysis will consider the relevant provisions of the LRA that grant trade unions the right to information and employers’ duty to disclose the information, to determine the balance between the interests of trade unions and employers regarding disclosure of information. It will also look at the position in the United Kingdom (UK) in order to determine whether there are lessons to be learned for South Africa.